Optimal Analysis of Tunnel Construction Methods through Cross Passage from Subway Shaft. (28th February 2018) - Song, Zhanping; Cao, Zhilin; Wang, Junbao; Wei, Shoufeng; Hu, Shichun; Niu, Zelin
Abstract : The conversion section of the cross passage and shaft is a priority concern in the stress transformation of a tunnel structure during subway underground excavation. In the construction of Subway Line 5 in Xi'an, China, the main line in the loess layer was constructed through the cross passage from the subway shaft of the Yue Deng Pavilion–San Dian Village Station tunnel section. Numerical simulation and field measurement were adopted to study the construction stability of the cross passage and shaft under two possible construction methods: the "shaft followed by cross passage construction" method and the "cross passage parallel shaft construction" method. The results showed that the surface deformation and plastic zone of the surrounding rock are similar under the two construction methods. However, of the two, the "cross passage parallel shaft construction" method was more advantageous in controlling the structural deformation of the original shaft and the stress distribution of the horsehead structure. The field monitoring data showed that the surface settlements and the deformation of the original shaft structures meet the requirement of control standards under the "cross passage parallel shaft construction" method.